Semantics for Accurate Conflict Detection in SMoVer: Specification, Detection and Presentation by Example - Altmanninger, Kerstin; Schwinger, Wieland; Kotsis, Gabriele (International journal of enterprise information systems, 2010)
In collaborative software development, the utilization of Version Control Systems (VCSs) is a must. For this, a multitude of pessimistic as well as optimistic VCSs for model artifacts emerged. Pessimistic approaches follow the lock-edit-unlock paradigm whereas optimistic approaches allow parallel editing of one resource, which are therefore the preferred ones. To be flexible for the ever increasing variety of modeling environments and languages such tools should be independent of the modeling environment and applicable to various modeling languages. Those VCS characteristics may implicate a lack of information for the conflict detection method by virtue of firstly receiving solely the state of an artifact without concrete editing operations and secondly due to unavailable knowledge about the semantics of a modeling language. However, in optimistic VCSs concurrent changes can result in conflicts and inconsistencies. In environment and language independent VCSs inconsistencies would even arise more often due to information losses. Hence, accurate conflict detection methods are indispensable for the realization of such VCSs. To tackle this task, the “Semantically enhanced Model Version Control System” SMoVer is presented. With SMoVer it is possible to specify the semantics of a modeling language, needed for conflict detection in order to provide more accurate conflict reports than other current environment and language independent VCSs. In this work, it is exemplified how semantics of a specific modeling language can be specified in SMoVer, how those specifications can improve the accuracy of conflict reports and finally how those can be presented to modelers.